Overview of Adductomics in Toxicology. Issue 2 (17th February 2023) - Lockridge, Oksana
Abstract: Adductomics is epidemiology at the molecular level. Untargeted adductomics compares levels of chemical adducts on albumin, hemoglobin, and DNA between healthy and exposed individuals. The goal is to determine a cause‐and‐effect relationship between chemical exposure and illness. Chemical exposures are not necessarily due to synthetic chemicals but are often due to oxidation products of naturally occurring lipids, for example, 4‐hydroxynonenal and acrolein produced by lipid peroxidation of arachidonic and linoleic acids. The preferred method used in adductomics is ultra‐high pressure liquid chromatography coupled to with nanoelectrospray tandem mass spectrometry. The mass of the adduct indicates its structure and identifies the chemical. The advantages of molecular epidemiology include information about the many toxicants to which a person is exposed over a period of weeks or months and the relative exposure levels. The disadvantage is the absence of information about the mechanism of toxicity. Untargeted adductomics examines albumin and hemoglobin adducts, which serve as biomarkers of exposure but do not identify the proteins and genes responsible for the toxicity. Targeted adductomics is used when the origin of the toxicity is known. This can be either an adducted protein, such as the butyrylcholinesterase protein modified by nerve agents, or a toxicant, such as acetaminophen. Untargeted adductomics methods have identified potential protein adduct biomarkers of breast cancer, colorectal cancer, childhood leukemia, and lung cancer. Adductomics is a new research area that offers structural insights into chemical exposures and a platform for the discovery of disease biomarkers. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC.